On the Validity of Grammatical Rules in Teaching Czech for Foreigners - Hrdlička, Milan (Bohemica Olomucensia, 2017)
In the foreign language learning process, a major role is played by linguodidactic grammatical rules taking balanced consideration of both the formal aspects and the speech dimension of a grammatical category or phenomenon. In Czech textbooks designed for other-language speakers we can find quite a few points of concern, especially formalism, i.e. considerable (and often exclusive) attention paid only to the grammatical form, without regard to its speech function. One of the crucial issues is the veracity, accuracy and validity of a linguo-didactic grammatical instruction. In the initial phase of foreign-language teaching, we approve of the necessity to simplify. Nonetheless, with the growing level of communicative competence of the other-language speaker, we demand an instruction of a higher quality. The character of the linguo-didactic grammatical rule depends on various factors, among the most significant are the level of the foreigner's knowledge of Czech and their first language, or their knowledge of other languages (typologically similar and genealogically related).
Keywords: grammar; Czech as a foreign language; linguodidactics; grammatical rule; didactic grammar; textbook of Czech for foreigners